MicroRNA-277 Modulates the Neurodegeneration Caused by Fragile X Premutation rCGG Repeats. - Tan, H.; Poidevin, M.; Li, H.; Chen, D.; Jin, P. (PLoS Genetics, 2012)
Fragile X-associated tremor/ataxia syndrome (FXTAS), a late-onset neurodegenerative disorder, has been recognized in older male fragile X premutation carriers and is uncoupled from fragile X syndrome. Using a Drosophila model of FXTAS, we previously showed that transcribed premutation repeats alone are sufficient to cause neurodegeneration. MiRNAs are sequence-specific regulators of post-transcriptional gene expression. To determine the role of miRNAs in rCGG repeat-mediated neurodegeneration, we profiled miRNA expression and identified selective miRNAs, including miR-277, that are altered specifically in Drosophila brains expressing rCGG repeats. We tested their genetic interactions with rCGG repeats and found that miR-277 can modulate rCGG repeat-mediated neurodegeneration. Furthermore, we identified Drep-2 and Vimar as functional targets of miR-277 that could modulate rCGG repeat-mediated neurodegeneration. Finally, we found that hnRNP A2/B1, an rCGG repeat-binding protein, can directly regulate the expression of miR-277. These results suggest that sequestration of specific rCGG repeat-binding proteins could lead to aberrant expression of selective miRNAs, which may modulate the pathogenesis of FXTAS by post-transcriptionally regulating the expression of specific mRNAs involved in FXTAS.